Impulse control disorders in advanced Parkinson's disease with dyskinesia: The ALTHEA study. Issue 11 (27th September 2017) - Biundo, Roberta; Weis, Luca; Abbruzzese, Giovanni; Calandra‐Buonaura, Giovanna; Cortelli, Pietro; Jori, Maria Cristina; Lopiano, Leonardo; Marconi, Roberto; Matinella, Angela; Morgante, Francesca; Nicoletti, Alessandra; Tamburini, Tiziano; et al.
Abstract: Background: Impulse control disorders and dyskinesia are common and disabling complications of dopaminergic treatment in Parkinson's disease. They may coexist and are possibly related. The objectives of this study were to assess the frequency and severity of impulse control disorders in Parkinson's disease patients with dyskinesia. Methods: The ALTHEA study enrolled 251 Parkinson's disease patients with various degrees of dyskinesia severity from 11 movement disorders centers in Italy. Each patient underwent a comprehensive assessment including Unified Dyskinesia Rating Scale and the Questionnaire for Impulsive Compulsive Disorders in Parkinson Disease‐Rating Scale. Results: There was an overall 55% frequency of impulse control disorder and related behaviors (36% were clinically significant). The positive patients were younger at disease diagnosis and onset and had higher Unified Dyskinesia Rating Scale historical and total score ( P = 0.001 and P = 0.02, respectively, vs negative). There was an increased frequency of clinically significant impulse control disorders in patients with severe dyskinesia ( P = 0.013), a positive correlation between the questionnaire total score and dopamine agonist dose ( P = 0.018), and a trend with levodopa dose. Conclusions: More than half of Parkinson's disease patients with dyskinesia have impulse control disorders and related behaviors, which are frequently clinically significant. Dopaminergic therapy total dose is associated with their severity. Clinicians should carefully assess patients with maladaptive behaviors and dyskinesia because they do not properly evaluate their motor and nonmotor status. © 2017 International Parkinson and Movement Disorder Society